Hesperidin inhibits HeLa cell proliferation through apoptosis mediated by endoplasmic reticulum stress pathways and cell cycle arrest. Issue 1 (December 2015) - Wang, Yaoxian; Yu, Hui; Zhang, Jin; Gao, Jing; Ge, Xin; Lou, Ge
Abstract Background Hesperidin (30, 5, 9-dihydroxy-40-methoxy-7-orutinosyl flavanone) is a flavanone that is found mainly in citrus fruits and has been shown to have some anti-neoplastic effects. The aim of the present study was to investigate the effect of hesperidin on apoptosis in human cervical cancer HeLa cells and to identify the mechanism involved. Methods Cells were treated with hesperidin (0, 20, 40, 60, 80, and 100 μM) for 24, 48, or 72 h and relative cell viability was assessed using the 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) assay. Results Hesperidin inhibited the proliferation of HeLa cells in a concentration- and time-dependent manner. Hesperidin-induced apoptosis in HeLa cells was characterized by increased nuclear condensation and DNA fragmentation. Furthermore, increased levels of GADD153/CHOP and GRP78 indicated hesperidin-induced apoptosis in HeLa cells involved a caspase-dependent pathway, presumably downstream of the endoplasmic reticulum stress pathway. Both of these proteins are hallmarks of endoplasmic reticulum stress. Hesperidin also promoted the formation of reactive oxygen species, mobilization of intracellular Ca2+, loss of mitochondrial membrane potential (ΔΨm), increased release of cytochrome c and apoptosis-inducing factor from mitochondria, and promoted capase-3 activation. It also arrested HeLa cells in the G0/G1 phase in the cell cycle by downregulating the expression of cyclinD1, cyclinE1, and cyclin-dependent kinase 2 at the protein level. The effect of hesperidin was also verified on the human colon cancer cell HT-29 cells. Conclusion We concluded that hesperidin inhibited HeLa cell proliferation through apoptosis involving endoplasmic reticulum stress pathways and cell cycle arrest.